PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI KERJA GURU TERHADAP DISIPLIN KERJA GURU SD NEGERI SEKECAMATAN BANDAR SEI. KIJANG KABUPATEN PELALAWAN - Sumarti Sumarti; Gimin Gimin; Erni Erni (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2022)
This study aims to (1) find out that the principal's leadership affects the teacher's work discipline, (2) work motivation affects the teacher's work discipline, (3) the principal's leadership and work motivation have a joint effect on teacher work discipline. The respondents to the study were teachers of State Elementary Schools in Bandar Sei Kijang District, Pelalawan Regency, totaling 176 people with a sample of 122. Data collection is carried out through the dissemination of questionnaires. The data analysis used is descriptive analysis, inferential statistical analysis. The reliability coefficient of the instrument is calculated using the cronbach alpha formula. The results showed that there was a positive and significant influence of the principal's leadership on teacher work discipline by 0.533, and there was a positive and significant influence of work motivation on teacher work discipline of 0.666. Meanwhile, together there is an influence of the principal's leadership and work motivation on teacher work discipline of 0.702.